2023
DOI: 10.1186/s41065-023-00289-6
|View full text |Cite
|
Sign up to set email alerts
|

NPM3 as a novel oncogenic factor and poor prognostic marker contributes to cell proliferation and migration in lung adenocarcinoma

Abstract: Background Lung cancer is the leading cause of cancer-related deaths worldwide, and despite recent advances in targeted therapies and immunotherapies, the clinical benefit remains limited. Therefore, there is an urgent need to further investigate the molecular mechanisms underlying lung cancer. The aim of this study was to investigate the expression and function of NPM3 in the tumor microenvironment of lung adenocarcinoma (LUAD). Methods We utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first time that NPM3 has been shown to stimulate tumorigenesis in vivo and, therefore, the present study uncovered NPM3 as a potential oncoprotein. While this study was under revision, another report demonstrated that NPM3 can stimulate proliferation and migration of lung adenocarcinoma cells in vitro ( 46 ). Accordingly, NPM3 inhibitors might be useful for prostate and lung cancer therapy.…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, this is the first time that NPM3 has been shown to stimulate tumorigenesis in vivo and, therefore, the present study uncovered NPM3 as a potential oncoprotein. While this study was under revision, another report demonstrated that NPM3 can stimulate proliferation and migration of lung adenocarcinoma cells in vitro ( 46 ). Accordingly, NPM3 inhibitors might be useful for prostate and lung cancer therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Nucleoplasmin-3 (NPM3), which we identi ed as a protein with a similar expression pattern to AGR2 in CRC, is an emerging oncoprotein primarily localised in the nucleus and nucleolus, where it exerts its function in ribosome biogenesis by regulating pre-rRNA synthesis and chromatin remodelling function when bound in a pentameric conformation with NPM1 [10,11]. In lung adenocarcinoma, NPM3 is positively correlated with proliferation, while in gastric cancer, it promotes PD-L1-mediated immune escape [12,13].…”
Section: Introductionmentioning
confidence: 99%